Profile of Diabetes Mellitus in Benign Protate Hyperplation's Patients with Urinary Retention in Dr. Soetomo 2016 - Adha, Ahmad Zaidan Ni'am Abu; I'tishom, Reny; Rizaldi, Fikri; Soebadi, Doddy (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: Benign prostatic hyperplasia (BPH) develops inevitably related to age in almost all men starting around the age of 40 years. LUTS is the most common manifestation of BPH. There were several risk factors that play a role in the BPH and LUTS, one of which is diabetes mellitus. The incidence of diabetes mellitus is increasing throughout the world. In 2015, it was estimated that 30.3 million Americans (9.4%) and 3.4 million Canadians (9.3%) were diagnosed with diabetes. About 5% - 10% are diagnosed with type I, and around 90% - 95% are diagnosed with type II. The burden of the disease caused by diabetes is quite high and continues to increase in every country. It is estimated that the global prevalence of people with diabetes in 2013 as many as 382 million people will increase to 592 million by 2035. The exact etiology of BPH is still unknown. Acute urinary retention (AUR) is the most frequent urological emergency. This study aims to find out the number of occurrences of diabetes mellitus in BPH patients with urinary retention in Dr. Soetomo General Hospital from January to December 2016. Methods: This research used descriptive research design. Population in this study was BPH patients with acute urinary retention in Dr. Soetomo General Hospital in 2016. The total sampling method was used. The variable studied was diabetes mellitus. The data was obtained from the patient's medical record. Results: In this study, 62 subjects were found with 11 subjects with positive diabetes mellitus (17.7%) and 43 subjects with negative diabetes mellitus (69.4%). Conclusion: From the results of the study, it was found that there were 17.7% of BPH patients with acute urinary retention who had diabetes mellitus.